TI_GERICHTE 52.2022.279 vom 13. Juli 2022 , Ordine di ripristino di un fondo fuori zona edificabile e incluso nel PUC-PEIP - TI Tribunale d'appello (2022)
Ordine di ripristino di un fondo fuori zona edificabile e incluso nel PUC-PEIP